CORRELATION RELATIONSHIPS BETWEEN MAIN AGRONOMICALLY VALUABLE TRAITS OF COTTON LINES (Modern American Journal of Biological and Environmental Sciences, 2025)
This article analyzes the correlation relationships between the duration of the growing season and economically valuable traits in different lines of medium-fiber cotton (Gossypium hirsutum L.). The study was conducted in the regions of Tashkent, Fergana, and Kashkadarya, where productivity, fiber yield, fiber breaking strength, seed weight, and other indicators were examined. The results revealed a high positive correlation between yield and the number of bolls (r = 0.84–0.91), and a moderate positive correlation between boll size and yield (r = 0.32–0.61). In some cases, a negative correlation was observed between earliness and yield. The findings provide a scientific and practical basis for breeding programs aimed at selecting early-ripening, high-yielding, and quality-stable cotton genotypes.